Pendidikan Mengenai Lingkungan Hidup dalam Rangka Pembangunan Berkelanjutan - R.F. Saragih (Universitas Negeri Malang, 2016)
he environment can be managed by legislation and by nonlegislation policies. One of the nonlegislation policies is the implementation of a subject matter designed to develop a positive understanding and attitude toward environment reservation, either formally through school institutions or informally by information and counseling. Given information about the importance of environment conservation, one will be able to participate in any efforts to protect and maintain their environment and, in turn, perform substainable national development